Analisis Peran Jaringan Bisnis terhadap Pengembangan Produk UMKM Kuliner: Studi Kualitatif pada Mie Jebew dan Dimsum Ares - Dita, Al’sha Prames Prames; Kartini, Mega Nur; Sulastri, Sulastri; Marselina, Resya Dwi (JURNAL MANAJEMEN DAN BISNIS, 2025)
This study aims to analyze the role of business networks in product development among culinary MSMEs, namely Mie Jebew and Dimsum Ares, in Pameungpeuk, Bandung Regency. The study is motivated by the limited empirical research on the utilization of informal business networks among culinary MSMEs in semi-rural areas. A descriptive qualitative research method was employed, with data collected through observation, in-depth interviews, and documentation. Data validity was ensured through triangulation, while data analysis was conducted using descriptive qualitative analysis supported by SWOT analysis. The findings indicate that informal business networks established through social relationships, customers, suppliers, as well as the use of digital platforms and online food delivery services, play a significant role in expanding market reach, increasing sales, and sustaining business continuity. Although these business networks are not yet formally managed, they contribute to enhancing the competitiveness of MSMEs. This study provides practical contributions for MSME actors in optimizing business networks as a strategy for business development.